Acid-induced demineralisation of human enamel as a function of time and pH observed using X-ray and polarised light imaging - Harper, RA; Shelton, RM; James, JD; Salvati, E; Besnard, C; Korsunsky, AM; Landini, G (Elsevier, 2020)
Acid-induced enamel demineralisation affects many individuals either by exposure to acidic diets, acidic gas pollution (dental erosion) or to dental plaque acids (dental caries). This study aimed to develop in situ X-ray and light imaging methods to determine progression of enamel demineralisation and the dynamic relationship between acid pH and mineral density. Hourly digital microradiograph time-lapse sequences showed the depth of enamel demineralisation in 500 µm thick sections progressed with time from the surface towards the dentine following a power-law function, which was 21% faster than the lateral demineralisation progression after exposure for 85 h to lactic acid (10%, pH 2.2). The minimum greyscale remaining (mineral content) within the induced enamel lesion followed an exponential decay, while the accumulated total greyscale loss with time was linear, which showed a constant anisotropic mineral release within the enamel architecture. This 85 h demineralisation method studied by polarised light microscopy time-lapse sequences showed that once the demineralisation front reached the enamel Hunter-Schreger bands, there was preferential demineralisation along those bands. Mineral density loss was linear with increasing pH acidity between pH 5.2 and pH 4.0 (with 0.4 pH increments) when incubated over a 3-week period exposed to 0.5% lactic acid. At pH 4.0, there was complete mineral loss in the centre of the demineralised area after the 3-week period and the linear function intercepted the x-axis at ~ pH 5.5, near the critical pH for hydroxyapatite (HAp). These observations showed how intrinsic enamel structure and pH affected the progression of demineralisation. STATEMENT OF SIGNIFICANCE: Hydroxyapatite crystallites (HAp) in human enamel dissolve when exposed to an acidic environment but little is known about how the intrinsic structures in enamel and pH influence the demineralisation kinetics. We have developed a time-lapse in situ microradiography method to quantify microscopic anisotropic mineral loss dynamics in response to an acid-only caries model. Correlation with polarised light microscopy time-lapse sequences showed that larger structures in enamel also influence demineralisation progression as demineralisation occurred preferentially along the Hunter-Schreger bands (decussating prismatic enamel). The pH-controlled enamel mineral release in a linear manner quantifying the relationship between HAp orientation and acid solubility. These findings should direct the development of improved anti-demineralisation/ remineralisation treatments to retain/ restore the natural intrinsic enamel structure.